The Effect of Management Control System and Leadership Style on Managerial Performance (An Empirical Studies on SOE Company in Bandung) - Sugianto Yusuf, Paulus; Haizam Mohd Saudi, Mohd; Nurmalasari, Tiara; Surayya Mohd Saudi, Nur (International Journal of Engineering and Technology, 2018)
The purpose of this study is to determine the effect of management control system and leadership style on managerial performance using explanatory. Unit of analysis of this study is the managers who work in state-owned companies manufacturing in Bandung. Populations of this study are the employees who officiate as a manager in state-owned companies in Bandung and who became the sample of this study are 109 managers. The results of this study indicate that there are significant simultaneously effect between management control system and leadership style on managerial performance. Partially management control system has positive influence on managerial performance, as well as the leadership style which is partially positive influence on managerial performance.